Phosphorylation and Alternative Translation on Wheat Germ Cell-Free Protein Synthesis of the DHBV Large Envelope Protein - David, Guillaume; Fogeron, Marie-Laure; Montserret, Roland; Lecoq, Lauriane; Page, Adeline; Delolme, Frédéric; Nassal, Michael; Böckmann, Anja (Frontiers in Molecular Biosciences, 2019)
Wheat-germ cell-free protein synthesis (WG-CFPS) is a potent platform for the high-yield production of proteins. It is especially of interest for difficult-to-express eukaryotic proteins, such as toxic and transmembrane proteins, and presents an important tool in high-throughput protein screening. Until recently, an assumed drawback of WG-CFPS was a reduced capacity for post-translational modifications. Meanwhile, phosphorylation has been observed in WG-CFPS; yet, authenticity of the respective phosphorylation sites remained unclear. Here we show that a viral membrane protein, the duck hepatitis B virus (DHBV) large envelope protein (DHBs L), produced by WG-CFPS, is phosphorylated upon translation at the same sites as DHBs L produced during DHBV infection of primary hepatocytes. Furthermore, we show that alternative translation initiation of the L protein, previously identified in virus-producing hepatic cells, occurs on WG-CFPS as well. Together, these findings further strengthen the high potential of WG-CFPS to include the reproduction of specific modifications proteins experience in vivo.